ANALISIS PENGARUH PERSEPSI PROFESI DAN MOTIVASI TERHADAP MINAT MAHASISWA MENJADI AKUNTAN PUBLIK - Febrianti, Reni (Journal of Industrial Engineering & Management Research, 2021)
This This research is to determine the interest of regular accounting students and P2K to become public accountants as measured by student perceptions and motivation. Public accountants play a role in improving the quality and credibility of financial information. This research was conducted on accounting study program students class of 2016 at the Faculty of Economics and Business, MH University. Thamrin. Determination of the sample using non probability sampling method with purposive sampling technique. The number of respondents used in this study were 40 people. The data collection method was conducted using a survey method with a questionnaire technique which was measured using a Likert scale. The results of this study indicate that tcount = 5,960> 1,683 (tcount> ttable) while the significance value obtained is 0,000 (Sig <0.05), it can be concluded that there is a significant influence between the perception variable of the profession and the student's interest in becoming a public accountant, so H0 is rejected. and H1 is accepted and that fcount = 44.064> 3.23 while the significance value obtained is 0.00 (sig <0.05) so it can be concluded that there is a significant influence between the variables of professional perception and motivation together with student interest and testing. coefficient of the Profession Perception variable.